Effect of Individual Behavior Towards Investment in National Saving Schemes On the Economy of Pakistan - Waqar, Munir; Jerom Kueh, Swee Hui; Muhammad Asraf, Abdullah; Muhammad Sadiq, Malik (Seybold Publication, 2023)
Investment and savings are an essential part of an economy and support pillars for long-term growth. Savings and investments play a vital role in the well-being of the individuals and public. The theory of planned behaviour discussed the individual supports the retirement behaviour, of individuals and their savings and investment decisions. National Saving schemes of Pakistan by the individuals are the main problem as this investment is mainly used by the government for its projects offering higher rates among avenues of other competitive institutions. The study was conducted to check and examine the impact of social, personal, and economic factors on the investment decisions of individual government employees in the National Savings Schemes of Pakistan. The sampling technique used was convenience sampling for 330 samples in Lahore and Gujranwala. Multiple regression was applied to check the variables' effects. The results showed that financial information, advocate recommendations, neutral information, and inflation significantly impact investment decisions. In contrast, Firm image/self-image and personal financial needs had insignificant results on investment decisions. The policymakers and Government must guide and bring more avenues in National Savings Schemes. The Government may fulfill other national savings scheme images and basic personal financial needs to increase savings. The national savings may be enhanced, and better financial information about its avenues may be provided through financial literacy and information to individual investors.